Clinical profiles of patients with primary sclerosing cholangitis in the elderly. (19th November 2014) - Tanaka, Atsushi; Tazuma, Susumu; Okazaki, Kazuichi; Tsubouchi, Hirohito; Inui, Kazuo; Takikawa, Hajime
Abstract Background In 2012 we conducted a nationwide survey for primary sclerosing cholangitis (PSC) and isolated IgG4‐related sclerosing cholangitis (IgG4‐SC) in Japan, and demonstrated the young as well as the elderly individuals were at higher risk for development of PSC. In the current study we aimed to further clarify the clinical profiles of PSC in the elderly, compared with PSC in the young and IgG4‐SC. Methods The design was a questionnaires‐based, multi‐center retrospective study. The enrolled subjects were patients with PSC and isolated IgG4‐SC diagnosed after 2005. Since the median of age of patients with PSC was 48.1, we defined those who developed the disease at the age older than 48.1 as PSC in the elderly, and the rest as PSC in the young. Results We defined 98 and 99 patients as PSC in the elderly and in the young, respectively. Although symptoms and biochemistries at presentation were similar, serum IgA and IgM levels were significantly higher and lower in the elderly PSC compared to the young PSC, respectively (P < 0.001, P < 0.001). The sensitivity and specificity of serum IgG4 levels were 89.5% and 88.9% for discriminating the elderly PSC and IgG4‐SC. In terms of complications, prevalence of IBD was 12% in the elderly PSC and 57% in the young PSC, the latter being comparable to those in Europe and the USA. Conclusion It is reasoned to conclude that PSC in the young resembles those in Europe and the USA in terms of the onset age and prevalence of IBD, while PSC in the elderly is really unique in Japan.